Changes in Salivary Fluoride Levels with a 2-minute Toothbrush Timer - Lisa Prihastari; Ramdha Al Farabi Rosdi; Bimo Rintoko (Universitas Muhammadiyah Yogyakarta, 2023)
The duration of tooth brushing deserves special attention since it is a factor that affects oral hygiene. The recommended duration for tooth brushing is 120 seconds, yet many people do not follow this suggestion. The relationship between the duration of tooth brushing and the fluoride level in saliva after brushing is still debatable. The study aims to determine the effectiveness of brushing teeth for 2 minutes on fluoride levels in the saliva of children aged 7-8 years. This experiment employed a pretest-posttest design with the control group. This single-blind study involved students from SDN 03 Pagi Pasar Minggu as a group with a manual toothbrush (control group) and SDN 19 Cempaka Putih as a group brushing teeth with a timer (intervention group), each of which consisted of 20 students selected using simple random sampling. Measurement fluoride level in saliva using UV-VIS Spectrophotometer TECAN Infinite M200 Pro®. The study lasted for approximately 3 weeks. The results of the independent t-test indicated no significant difference in fluoride levels between the intervention and the control group (p0.05), although the mean score of the intervention group was higher than the control group. In conclusion, a 2-minute toothbrush timer had the same ability as a manual toothbrush to increase the fluoride level in the saliva of children aged 7-8 years.